2017
DOI: 10.1101/145268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Driver pattern identification over the gene co-expression of drug response in ovarian cancer by integrating high throughput genomics data

Abstract: The multiple types of high throughput genomics data create a potential opportunity to identify driver pattern in ovarian cancer, which will acquire some novel and clinical biomarkers for appropriate diagnosis and treatment to cancer patients. However, it is a great challenging work to integrate omics data, including somatic mutations, Copy Number Variations (CNVs) and gene expression profiles, to distinguish interactions and regulations which are hidden in drug response dataset of ovarian cancer. To distinguis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Gene mutations and copy number variations have been identified in ovarian cancer, which contribute to oncogenesis, ovarian cancer progression, and acquired chemoresistance (Lu et al., ; Zhao, Sun, & Zhao, ). Delineation of gene mutations and copy number variations in ovarian cancer could not only provide insight into the interplay of mutated genes and their encoded proteins in driving tumorigenesis and tumor progression, but it could also lead to identification of diagnostic and prognostic biomarkers for primary and recurrent ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Gene mutations and copy number variations have been identified in ovarian cancer, which contribute to oncogenesis, ovarian cancer progression, and acquired chemoresistance (Lu et al., ; Zhao, Sun, & Zhao, ). Delineation of gene mutations and copy number variations in ovarian cancer could not only provide insight into the interplay of mutated genes and their encoded proteins in driving tumorigenesis and tumor progression, but it could also lead to identification of diagnostic and prognostic biomarkers for primary and recurrent ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…29 Another study has shown that FGF22 and BRCA1 affect the thyroid hormone pathway in ovarian cancer. 30 Our results suggested that FGF22 and related TFs may affect signaling transduction pathways and carcinogenic pathways. However, to our knowledge, no study has reported the effect of FGF22 on lung cancer.…”
Section: Discussionmentioning
confidence: 63%